From busts to portraits: the Twelve Caesars beyond twelve faces - Carminati, Luis Henrique (Romanitas - Revista de Estudos Grecolatinos, 2024)
Images have been part of human communication long before the invention of writing. The construction of an imagetic discourse delineates layers of meanings, senses, and identification. Thus, images can establish communication networks based on their productive context and temporality, but also through reinterpretation and re-reading in other environments and circumstances, which can add new layers. In this way, the book "Twelve Caesars: Images of Power from the Ancient World to the Modern" - the subject of this review - addresses the different interpretations and re-readings produced about the Twelve Caesars, the family, and the imperial system, thereby understanding their uses and interactions with other temporalities, which, through these images, sought to elaborate discursive forms aligned with specific interests.